The Creative Thinking Skills Profile of Primary Education’s Perspective Teacher - Adzimatnur Muslihasari; Herawati Susilo; Ibrohim Ibrohim (Universitas Negeri Malang, 2024)
This study aims to analyze the creative thinking skills of primary education’s prospective teachers in science learning. This study uses a descriptive survey to obtain quantitative data without special treatment. The population is students of PGSD Universitas Islam Raden Rahmat for the 2022/2023 academic year who program science courses (125 students). The sample was selected by random sampling technique, which was 84 students. Creative thinking skills are measured by an essay test totaling 8 questions that refer to indicators of fluency, flexibility, originality, and elaboration. The data was analyzed descriptively by calculating the percentage of each indicator to be further adjusted to the level of creative thinking indicator. The results show that students' creative thinking skills is still low in all indicators and included in the non-creative level. Creative thinking skills on the 'fluency' indicator received ‘enough’, while 'flexibility', 'originality', and 'elaboration' were still at the 'low' and 'very low'.